Evaluating an australian emergency nurse practitioner candidate training program. Issue 4 (November 2017) - Plath, Sharyn J.; Wright, Mary; Hocking, Julia
Abstract: Nurse Practitioners (NPs) receive core clinical training at master's level, with their employer providing the opportunity to upskill in clinical and procedural competencies. It is increasingly recognised that this generic education requires supplementary training for operating effectively within a specific clinical environment. In this paper we describe a pilot program designed to train Australian NP Candidates to work effectively within the Emergency Department Fast Track model of care. The training program consisted of a 12-month period: four hours in-house training per week over two semesters, running concurrently with the NP candidate's University semesters, and 3 months' clinical practice to consolidate. The training team defined milestones for Semesters one and two, and developed a case review form to assess application of the candidate's knowledge in new clinical situations, as well as check for gaps in understanding. A clinical skills guide was developed for the candidate to work toward, and a comprehensive assessment was carried out at two time points in the training program. Feedback was obtained from the mentors and the candidate at the end point of the training program, and has been used to refine the program for 2017. This in-house training program provided specialised, evidence-based training for the emergency department environment, resulting in development of the nurse practitioner candidate as a high functioning team member.